Insights into post‐polymerisation modification of bio‐based unsaturated itaconate and fumarate polyesters via aza‐michael addition: Understanding the effects of CC isomerisation. Issue 17 (9th August 2018) - Farmer, T. J.; Macquarrie, D. J.; Comerford, J. W.; Pellis, A.; Clark, J. H.
ABSTRACT: Development of renewable bio‐based unsaturated polyesters is undergoing a renaissance, typified by the use of itaconate and fumarate monomers. The electron‐deficient CC bond found on the corresponding polyesters allows convenient post‐polymerisation modification to give a wide range of polymer properties; this is notably effective for the addition of nucleophilic pendants. However, preservation of unsaturated functionality is blighted by two undesirable side‐reactions, branching/crosslinking and CC isomerisation. Herein, a tentative kinetic study of diethylamine addition to model itaconate and fumarate diesters highlights the significance of undesirable CC isomerisation. In particular, it shows that reversible isomerisation from itaconate to mesaconate (a poor Michael acceptor) is in direct competition with aza‐Michael addition, where the amine Michael donor acts as an isomerisation catalyst. We postulate that undesired formation of mesaconate is responsible for the long reaction times previously reported for itaconate polyester post‐polymerisation modification. This study illustrates the pressing need to overcome this issue of CC isomerisation to enhance post‐polymerisation modification of bio‐based unsaturated polyesters. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1935–1945 Abstract : Undesirable regio‐isomerisation of CC in itaconates is found to be promoted by alkylamines during the intended aza‐Michael addition. Quantitive addition is possible but only with long reaction times, allowing the mesaconate regio‐isomer to revert back to itaconate. Regio‐selectivity to the itaconate adduct over the mesaconate was also confirmed. This study will assist future efforts to optimise post‐polymerisation of bio‐based unsaturated polyesters.